Climate change impacts on agriculture's southern frontier – Perspectives for farming in North Patagonia - del Barrio, Ricardo Alfredo (2020)
Fil: del Barrio, Ricardo. Universidad Nacional de Río Negro, Escuela de Producción, Tecnología y Medio Ambiente. Viedma, Argentina.